Preparation method of adsorbing material for treating cadmium ion wastewater
The adsorption materials formed by loading and cross-linking polymerization on the surface of the foam iron matrix have been solved, and the cadmium ion adsorption efficiency and selectivity in the prior art have been achieved, efficient cadmium ion removal and wide pH range stability have been achieved, which has significantly improved the Sewage treatment effect.
Patent Information
- Application Number
- CN202411300160.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2024-12-24
AI Technical Summary
The existing adsorption materials have insufficient cadmium ion adsorption removal efficiency and selectivity, making it difficult to effectively treat cadmium ion-containing wastewater, and have poor stability over a wide pH range.
The construction of amino substitution and cross-linked polyterephthalamide-mercaptopropylene succinate is carried out by loading chain polythiol succinate on the surface of the iron foam matrix to form adsorption with strong affinity and selectivity Material.
Excellent cadmium ion adsorption removal performance, high cadmium ion selectivity and wide pH range adaptability are achieved, significantly improving the effect of wastewater treatment.
Smart Images

Figure CN119175083A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of adsorption materials for wastewater treatment, in particular to a method for preparing an adsorption material for treating cadmium ion wastewater. Background Art
[0002] In industries such as electroplating, electrolysis, metal mining and smelting, textile printing and dyeing, and paint production, the generation of wastewater containing cadmium ions is inevitable. The cadmium ions in these wastewaters are extremely biologically toxic, and their impact on the environment and human health cannot be ignored. Therefore, it is crucial to develop efficient and environmentally friendly treatment technologies.
[0003] The treatment of wastewater containing cadmium ions is a major challenge in the current environmental protection field. Cadmium ions not only cause serious damage to the ecological environment, but also pose a huge threat to human health. At present, the commonly used treatment methods include:
[0004] 1. Chemical precipitation method: Cadmium ions are precipitated by adding chemical reagents, but this method is prone to secondary pollution and has high treatment costs.
[0005] 2. Electrolysis: Remove cadmium ions through electrolysis, but the high energy consumption limits its large-scale application.
[0006] 3. Membrane separation method: Use membrane technology to separate cadmium ions, but the membrane is expensive and easily contaminated and clogged, and the maintenance cost is high.
[0007] 4. Adsorption method: Cadmium ions are removed through adsorption materials, which has the advantages of no secondary pollution and no need for high-energy consumption equipment and process.
[0008] However, existing adsorption materials are insufficient in terms of cadmium ion adsorption removal efficiency and selectivity, which has become a technical bottleneck in the development of adsorption treatment methods. Summary of the invention
[0009] In order to overcome the shortcomings of the prior art, the present invention provides a method for preparing an adsorbent material for treating cadmium ion wastewater. The adsorbent material prepared by the method has excellent cadmium ion adsorption and removal performance, high cadmium ion selectivity and adaptability to a wide pH range.
[0010] The technical solution adopted by the present invention to solve its technical problem is:
[0011] The present invention provides a method for preparing an adsorbent material for treating cadmium ion wastewater, comprising the following steps performed in sequence:
[0012] Step [1] Loading chain polythiocarboxylic acid propylene glycol on the surface of the foamed iron matrix;
[0013] Step [2] Substitution of the amino group of poly(propylene glycol mercapto succinate);
[0014] Step [3] constructs cross-linked poly(terephthalamide)-mercaptosuccinate on the surface of the foamed iron matrix to obtain the adsorption material.
[0015] Preferably, the step [1] specifically includes the following operations:
[0016] a1. Add mercaptosuccinic acid, 1,3-propylene glycol and ethane sulfonic acid to deionized water and mix to form an inorganic base liquid; add cumene hydroperoxide and propylbenzene to anhydrous ethanol and mix to form an organic additive liquid; add a certain amount of organic additive liquid to the inorganic base liquid and mix to form a synthetic liquid;
[0017] a2. Immerse the foamed iron sample in the synthetic solution, heat it in a water bath to 50-70°C, react at a constant temperature for 8-12 hours, remove the sample and rinse it with ethanol several times, and then wash it with deionized water several times to obtain a foamed iron with a surface loaded with chain polythiosulfate propylene glycol, recorded as intermediate A.
[0018] Preferably, in step a1, the concentration of mercaptosuccinic acid in the inorganic base liquid is 120g / L-150g / L, the concentration of 1,3-propylene glycol is 100mL / L-170mL / L, and the concentration of ethanesulfonic acid is 40mL / L-80mL / L; the concentration of cumene hydroperoxide in the organic additive liquid is 40mL / L-70mL / L, and the concentration of propylbenzene is 10mL / L-20mL / L; the volume ratio between the organic additive liquid and the inorganic base liquid in the synthetic liquid is 1-2:7-9.
[0019] Preferably, in step a2, the weight of the foamed iron immersed in each liter of the synthetic liquid is 230-270 g.
[0020] Preferably, the step [2] specifically includes the following operations:
[0021] b1. Add cerium ammonium nitrate, ammonium sulfamate, ferric nitrate and sec-butyl alcohol to deionized water and mix to form a replacement solution;
[0022] b2. Immerse the intermediate A in the substitution solution, heat in a water bath to 40-50°C, and react for 2-4 hours to complete the amino substitution formation of the chain polythiolsuccinic acid propylene glycol on the surface of the foamed iron to obtain the intermediate B.
[0023] Preferably, the concentration of ammonium cerium nitrate in the replacement solution is 160g / L-200g / L, the concentration of ammonium sulfamate is 80g / L-170g / L, the concentration of ferric nitrate is 60g / L-80g / L, and the concentration of sec-butanol is 50mL / L-90mL / L.
[0024] Preferably, in step b2, the weight of the intermediate A immersed in each liter of the replacement liquid is 50-90 g.
[0025] Preferably, the step [3] specifically includes the following operations:
[0026] c1. Adding terephthalic acid and azobisisoheptanenitrile to dimethyl sulfoxide, mixing to form a base liquid; adding sulfamic acid to deionized water, mixing to form an additive liquid; adding a certain amount of the additive liquid to the base liquid, mixing to form a construction liquid;
[0027] c2. Immerse the intermediate B in the construction solution, heat it to 60-80° C. in a water bath, and react at a constant temperature for 4-6 hours to obtain a foamed iron having a surface loaded with cross-linked polyterephthalamide-mercaptosuccinate, which is the adsorption material.
[0028] Preferably, in step c1, the amount of phthalic acid added to each liter of the base liquid is 140-210 g, and the amount of azobisisoheptanenitrile added is 30-90 g; the concentration of aminosulfonic acid in the additive liquid is 120 g / L-140 g / L; and the volume ratio between the additive liquid and the base liquid in the construction liquid is 1-3:3-4.
[0029] Preferably, in step c2, the weight of the intermediate B immersed in each liter of the construction solution is 180-260 g.
[0030] Positive effects of the present invention: The adsorbent material prepared by the method of the present invention is based on the polymerization of mercaptosuccinic acid and propylene glycol on the surface of the foamed iron matrix to form a chain of mercaptosuccinic acid propylene glycol, and then the amino group is substituted and then a cross-linked structure polyterephthalamide-mercaptosuccinic acid propylene glycol is formed through a condensation reaction with terephthalic acid. Based on the above structural characteristics, the mercapto group belongs to a soft base, and the sulfur atom of the mercapto group has a strong affinity for soft Lewis acid cadmium ions. Therefore, the adsorbent material has strong adsorption and selectivity for cadmium ions; at the same time, the amide group and the mercapto group are polar groups that can react with water molecules through hydrogen bonds, so that the cadmium ion-containing wastewater wets the adsorbent material, thereby promoting the adsorption of cadmium ions on the mercapto group; in addition, the adsorbent material can maintain its physical and chemical stability in a wide pH range.
[0031] In conclusion, the adsorption material prepared according to the present invention has excellent cadmium ion adsorption and removal performance, high cadmium ion selectivity and adaptability in a wide pH range. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 It is a schematic diagram of the preparation process of the adsorption material of the present invention;
[0033] Figure 2 It is the structure of the cross-linked polyterephthalamide-propylene mercaptosuccinate described in the present invention;
[0034] Figure 3It is the cadmium ion adsorption removal rate in simulated cadmium ion-containing sewage under different pH conditions of Example 1, Comparative Example 1 and Comparative Example 2 of the present invention;
[0035] Figure 4 The cadmium ion in the wastewater simulated by Example 1, Comparative Example 1 and Comparative Example 2 of the present invention is Cd at pH 7. 2+ , Cu 2+ and Ag + adsorption removal rate. DETAILED DESCRIPTION
[0036] Reference Figure 1 The present invention provides a method for preparing an adsorbent material for treating cadmium ion wastewater, comprising the following steps performed in sequence:
[0037] Step [1] loading chain polythiosulfate propylene glycol succinate on the surface of the foamed iron matrix specifically comprises the following operations:
[0038] a1. Add mercaptosuccinic acid, 1,3-propylene glycol, and ethane sulfonic acid to deionized water to form an inorganic base liquid having a mercaptosuccinic acid concentration of 120 g / L-150 g / L, a 1,3-propylene glycol concentration of 100 mL / L-170 mL / L, and an ethane sulfonic acid concentration of 40 mL / L-80 mL / L; add cumene hydroperoxide and propylbenzene to anhydrous ethanol to form an organic additive liquid having a cumene hydroperoxide concentration of 40 mL / L-70 mL / L and a propylbenzene concentration of 10 mL / L-20 mL / L; add the organic additive liquid to the inorganic base liquid in a volume ratio of 1 to 2:7 to 9 to form a synthetic liquid;
[0039] a2. Immerse the foamed iron sample in the synthetic liquid (the weight of the foamed iron immersed in each liter of the synthetic liquid is 230-270g), heat it in a water bath to 50-70°C, react it at a constant temperature for 8-12 hours, take out the sample and rinse it with ethanol for several times, and then wash it with deionized water for several times to obtain foamed iron with chain polymercapto succinic acid propylene glycol loaded on the surface, which is recorded as intermediate A. The structural formula of the chain polymercapto succinic acid propylene glycol is:
[0040]
[0041] Step [2] The amino group of poly(propylene glycol mercapto succinate) is substituted and formed, which specifically comprises the following operations:
[0042] b1. The ammonium cerium nitrate, ammonium sulfamate, ferric nitrate and sec-butanol were added to deionized water to form a mixture of ammonium cerium nitrate at a concentration of 160 g / L-200 g / L, ammonium sulfamate at a concentration of 80 g / L-170 g / L, ferric nitrate at a concentration of 60 g / L-80 g / L, and sec-butanol at a concentration of 50 mL / L-90 mL / L of the replacement solution;
[0043] b2. Immerse the intermediate A in the substitution liquid (the weight of the intermediate A immersed in each liter of the substitution liquid is 50-90g), heat it in a water bath to 40-50°C, and react for 2-4 hours to complete the amino substitution formation of the chain polymercapto succinic acid propylene glycol on the surface of the foamed iron to obtain the intermediate B. The amino group substitution structural formula of the chain polymercapto succinic acid propylene glycol is:
[0044]
[0045] Step [3] constructs cross-linked polyterephthalamide-thiosuccinate on the surface of the foamed iron matrix, specifically comprising the following operations:
[0046] c1. Add terephthalic acid and azobisisoheptanenitrile to dimethyl sulfoxide and mix to form a base solution (the amount of phthalic acid added per liter of the base solution is 140-210 g, and the amount of azobisisoheptanenitrile added is 30-90 g); add sulfamic acid to deionized water and mix to form an additive solution having a sulfamic acid concentration of 120 g / L-140 g / L; add the additive solution to the base solution in a volume ratio of 1 to 3:3 to 4 to form a construction solution;
[0047] c2. Immerse the intermediate B in the construction liquid (the weight of the intermediate B immersed in each liter of the construction liquid is 180-260g), heat it in a water bath to 60-80°C, and react at a constant temperature for 4-6 hours to obtain a foamed iron loaded with cross-linked polyterephthalamide-mercaptosuccinate, and finally obtain the adsorption material. The structure of the cross-linked polyterephthalamide-mercaptosuccinate is as follows: Figure 2 shown.
[0048] The preferred embodiments of the present invention are described below by way of example.
[0049] Example 1
[0050] Preferred embodiment 1 of the present invention provides a method for preparing an adsorbent material for treating cadmium ion wastewater, comprising the following steps performed in sequence:
[0051] Step [1] loading chain polythiosulfate propylene glycol succinate on the surface of the foamed iron matrix specifically comprises the following operations:
[0052] a1. Add mercaptosuccinic acid, 1,3-propylene glycol and ethane sulfonic acid to deionized water to form an inorganic base liquid having a mercaptosuccinic acid concentration of 145 g / L, a 1,3-propylene glycol concentration of 150 mL / L and an ethane sulfonic acid concentration of 70 mL / L; add cumene hydroperoxide and propylbenzene to anhydrous ethanol to form an organic additive liquid having a cumene hydroperoxide concentration of 55 mL / L and a propylbenzene concentration of 18 mL / L; add the organic additive liquid to the inorganic base liquid in a volume ratio of 1:8 and add the organic additive liquid to the inorganic base liquid to form a synthetic liquid;
[0053] a2. Immerse the foamed iron sample in the synthetic liquid (the weight of the foamed iron immersed in each liter of the synthetic liquid is 245 g), heat it to 65°C in a water bath, react for 10 hours at a constant temperature, take out the sample and rinse it three times with ethanol, and then wash it twice with deionized water to obtain foamed iron with chain polythiosulfate succinate loaded on the surface, which is recorded as intermediate A.
[0054] Step [2] The amino group of poly(propylene glycol mercapto succinate) is substituted and formed, which specifically comprises the following operations:
[0055] b1. The ammonium cerium nitrate, ammonium sulfamate, ferric nitrate and sec-butanol were added to deionized water and mixed to form a cerium ammonium nitrate concentration of 190g / L, ammonium sulfamate concentration of 150g / L, ferric nitrate concentration of 70g / L, sec-butanol concentration of 80mL / L of the replacement solution;
[0056] b2. Immerse intermediate A in the substitution liquid (the weight of intermediate A immersed in each liter of the substitution liquid is 80 g), heat to 46° C. in a water bath, and react for 4 hours to complete the amino substitution formation of the chain polythiolsuccinic acid propylene glycol on the surface of the foamed iron to obtain intermediate B.
[0057] Step [3] constructs cross-linked polyterephthalamide-thiosuccinate on the surface of the foamed iron matrix, specifically comprising the following operations:
[0058] c1. Add terephthalic acid and azobisisoheptanenitrile to dimethyl sulfoxide and mix to form a base solution (the amount of phthalic acid added per liter of the base solution is 170 g, and the amount of azobisisoheptanenitrile added is 80 g); add sulfamic acid to deionized water to form an additive solution having a sulfamic acid concentration of 130 g / L; add the additive solution to the base solution in a ratio of 2:3 by volume to form a construction solution;
[0059] c2. The intermediate B is immersed in the construction liquid (the weight of the intermediate B immersed in each liter of the construction liquid is 220 g), heated to 70° C. in a water bath, and reacted at a constant temperature for 5 hours to obtain a foamed iron with a surface loaded with cross-linked polyterephthalamide-mercaptosuccinate, and finally the adsorption material is obtained, which is recorded as Example 1.
[0060] Comparative Example 1
[0061] This comparative example 1 provides a method for preparing an adsorbent material, the steps are as follows:
[0062] The chain-like polythiosulfate propylene glycol succinate is loaded on the surface of the foamed iron matrix, specifically comprising the following operations:
[0063] a1. Add mercaptosuccinic acid, 1,3-propylene glycol and ethane sulfonic acid to deionized water to form an inorganic base liquid having a mercaptosuccinic acid concentration of 130 g / L, a 1,3-propylene glycol concentration of 160 mL / L and an ethane sulfonic acid concentration of 60 mL / L; add cumene hydroperoxide and propylbenzene to anhydrous ethanol to form an organic additive liquid having a cumene hydroperoxide concentration of 50 mL / L and a propylbenzene concentration of 15 mL / L; add the organic additive liquid to the inorganic base liquid in a volume ratio of 2:7 to add the organic additive liquid to the inorganic base liquid to form a synthetic liquid;
[0064] a2. The foamed iron sample is immersed in the synthetic liquid (the weight of the foamed iron immersed in each liter of the synthetic liquid is 260g), heated to 60°C in a water bath, reacted at a constant temperature for 9 hours, the sample is taken out and rinsed twice with ethanol, and then washed three times with deionized water to obtain a foamed iron with a surface loaded with chain polythiolsuccinate propylene glycol, which is recorded as Comparative Example 1.
[0065] Comparative Example 2
[0066] This comparative example 2 provides a method for preparing an adsorbent material, comprising the following steps performed in sequence:
[0067] Step [1] loading chain polythiocarboxylic acid propylene glycol on the surface of the foamed iron matrix specifically comprises the following operations:
[0068] a1. Add mercaptosuccinic acid, 1,3-propylene glycol and ethane sulfonic acid to deionized water to form an inorganic base liquid having a mercaptosuccinic acid concentration of 130 g / L, a 1,3-propylene glycol concentration of 120 mL / L and an ethane sulfonic acid concentration of 50 mL / L; add cumene hydroperoxide and propylbenzene to anhydrous ethanol to form an organic additive liquid having a cumene hydroperoxide concentration of 60 mL / L and a propylbenzene concentration of 12 mL / L; add the organic additive liquid to the inorganic base liquid in a volume ratio of 1:7 to form a synthetic liquid;
[0069] a2. Immerse the foamed iron sample in the synthetic liquid (the weight of the foamed iron immersed in each liter of the synthetic liquid is 240 g), heat it to 60°C in a water bath, react at a constant temperature for 9 hours, take out the sample and rinse it three times with ethanol, and then wash it twice with deionized water to obtain foamed iron with chain polythiolsuccinate propylene glycol loaded on the surface, which is recorded as intermediate A.
[0070] Step [2] The amino group of poly(propylene glycol mercapto succinate) is substituted and formed, which specifically comprises the following operations:
[0071] b1. The ammonium cerium nitrate, ammonium sulfamate, ferric nitrate and sec-butanol were added to deionized water and mixed to form a cerium ammonium nitrate concentration of 170g / L, ammonium sulfamate concentration of 90g / L, ferric nitrate concentration of 70g / L, sec-butanol concentration of 80mL / L of the replacement solution;
[0072] b2. Immerse the intermediate A in the substitution liquid (the weight of the intermediate A immersed in each liter of the substitution liquid is 80 g), heat it to 45°C in a water bath, and react for 3 hours to complete the amino substitution formation of the chain polythiolsuccinic acid propylene glycol on the surface of the foamed iron, and obtain the adsorption material, which is recorded as Comparative Example 2.
[0073] In order to analyze the cadmium ion adsorption and removal performance and pH range adaptability of Example 1, Comparative Example 1 and Comparative Example 2 in treating cadmium ion-containing sewage, cadmium nitrate was added to deionized water to prepare simulated cadmium ion-containing sewage with a cadmium nitrate concentration of 10 mg / L. The pH value of the simulated cadmium ion-containing sewage prepared above was adjusted with hydrochloric acid and sodium hydroxide to obtain each simulated cadmium ion-containing sewage with a pH value of 3, 5, 7, and 9. 25 g of adsorption material (Example 1, Comparative Example 1, Comparative Example 2) was placed in each liter of the corresponding simulated sewage for cadmium ion adsorption treatment, and the treatment time was 100 min. The Cd content of the corresponding simulated sewage after the adsorption treatment was measured by inductively coupled plasma emission spectrometer (ICP-OES). 2+ Concentration, calculate Cd 2+ Adsorption removal rate, the results are as follows Figure 3 As shown in Example 1, the pH values of Cd 2+ The removal rates of Cd in Comparative Examples 1 and 2 were not less than 90%. 2+ The removal rate of Cd was significantly lower than that of Example 1. 2+ The removal rate of ions, and the comparative examples 1 and 2Cd 2+ The removal rate of ions is significantly affected by changes in the pH value of cadmium ion-containing wastewater.
[0074] In addition, in order to analyze the cadmium ion selectivity of Example 1, Comparative Example 1 and Comparative Example 2 in treating cadmium ion-containing sewage, cadmium nitrate, copper sulfate and silver nitrate were added to deionized water to form cadmium ion simulated sewage, copper ion simulated sewage and silver ion simulated sewage with a cadmium nitrate concentration of 10 mg / L, a copper sulfate concentration of 10 mg / L and a silver nitrate concentration of 10 mg / L, respectively. The pH value of the prepared cadmium ion, copper ion and silver ion simulated sewage was adjusted to 7 by hydrochloric acid and sodium hydroxide. 25g of adsorption material (Example 1, Comparative Example 1, Comparative Example 2) was placed in each liter of the corresponding simulated sewage for cadmium ion adsorption treatment, and the treatment time was 100min. The Cd of the corresponding simulated sewage after the adsorption treatment was measured by inductively coupled plasma emission spectrometer (ICP-OES). 2+ , Cu 2+ 、Ag + Ion concentration, calculate Cd 2+ , Cu 2+ and Ag + Ion adsorption removal rate, the results are as follows Figure 4 As shown, Example 1Cd 2+ , Cu 2+ and Ag + The adsorption removal rates of ions were 92%, 5% and 6% respectively. 2+ , Cu 2 + and Ag + The adsorption removal rates of ions were 16%, 14% and 12% respectively. 2+ , Cu 2+ and Ag + The adsorption removal rates of ions were 24%, 11% and 16% respectively. Obviously, Example 1 has a significant effect on the removal of Cd 2+ Ions have obvious selective adsorption and removal performance.
[0075] In summary, the adsorption material prepared according to the present invention has excellent cadmium ion adsorption and removal performance, high cadmium ion selectivity and adaptability to a wide pH range.
[0076] To illustrate in further detail, three additional examples are provided below.
[0077] Example 2
[0078] Preferred embodiment 2 of the present invention provides a method for preparing an adsorbent material for treating cadmium ion wastewater, comprising the following steps performed in sequence:
[0079] Step [1] loading chain polythiosulfate propylene glycol succinate on the surface of the foamed iron matrix specifically comprises the following operations:
[0080] a1. Add mercaptosuccinic acid, 1,3-propylene glycol and ethane sulfonic acid to deionized water to form an inorganic base liquid having a mercaptosuccinic acid concentration of 120 g / L, a 1,3-propylene glycol concentration of 100 mL / L and an ethane sulfonic acid concentration of 40 mL / L; add cumene hydroperoxide and propylbenzene to anhydrous ethanol to form an organic additive liquid having a cumene hydroperoxide concentration of 70 mL / L and a propylbenzene concentration of 20 mL / L; add the organic additive liquid to the inorganic base liquid in a volume ratio of 2:7 to add the organic additive liquid to the inorganic base liquid to form a synthetic liquid;
[0081] a2. Immerse the foamed iron sample in the synthetic liquid (the weight of the foamed iron immersed in each liter of the synthetic liquid is 230 g), heat it to 50°C in a water bath, react for 12 hours at a constant temperature, take out the sample and rinse it with ethanol for several times, and then wash it with deionized water for several times to obtain foamed iron with chain polythiosulfate succinate loaded on the surface, which is recorded as intermediate A.
[0082] Step [2] The amino group of poly(propylene glycol mercapto succinate) is substituted and formed, which specifically comprises the following operations:
[0083] b1. The ammonium cerium nitrate, ammonium sulfamate, ferric nitrate and sec-butanol were added to deionized water and mixed to form a cerium ammonium nitrate concentration of 160g / L, ammonium sulfamate concentration of 80g / L, ferric nitrate concentration of 80g / L, sec-butanol concentration of 50mL / L of the replacement solution;
[0084] b2. Immerse intermediate A in the substitution liquid (the weight of intermediate A immersed in each liter of the substitution liquid is 50 g), heat to 40°C in a water bath, and react for 4 hours to complete the amino substitution formation of the chain polythiolsuccinic acid propylene glycol on the surface of the foamed iron to obtain intermediate B.
[0085] Step [3] constructs cross-linked polyterephthalamide-thiosuccinate on the surface of the foamed iron matrix, specifically comprising the following operations:
[0086] c1. Add terephthalic acid and azobisisoheptanenitrile to dimethyl sulfoxide and mix to form a base solution (the amount of phthalic acid added per liter of the base solution is 140 g, and the amount of azobisisoheptanenitrile added is 30 g); add sulfamic acid to deionized water to form an additive solution having a sulfamic acid concentration of 140 g / L; add the additive solution to the base solution in a ratio of 2:3 by volume to form a construction solution;
[0087] c2. The intermediate B is immersed in the construction liquid (the weight of the intermediate B immersed in each liter of the construction liquid is 180 g), heated to 80° C. in a water bath, and reacted at a constant temperature for 4 hours to obtain a foamed iron with a surface loaded with cross-linked polyterephthalamide-mercaptosuccinate, and finally the adsorption material is obtained.
[0088] Example 3
[0089] Preferred embodiment 3 of the present invention provides a method for preparing an adsorbent material for treating cadmium ion wastewater, comprising the following steps performed in sequence:
[0090] Step [1] loading chain polythiocarboxylic acid propylene glycol on the surface of the foamed iron matrix specifically comprises the following operations:
[0091] a1. Add mercaptosuccinic acid, 1,3-propylene glycol and ethane sulfonic acid to deionized water to form an inorganic base liquid having a mercaptosuccinic acid concentration of 150 g / L, a 1,3-propylene glycol concentration of 170 mL / L and an ethane sulfonic acid concentration of 80 mL / L; add cumene hydroperoxide and propylbenzene to anhydrous ethanol to form an organic additive liquid having a cumene hydroperoxide concentration of 40 mL / L and a propylbenzene concentration of 10 mL / L; add the organic additive liquid to the inorganic base liquid in a volume ratio of 1 to 2:7 to 9 to form a synthetic liquid;
[0092] a2. Immerse the foamed iron sample in the synthetic liquid (the weight of the foamed iron immersed in each liter of the synthetic liquid is 270 g), heat it to 70°C in a water bath, react at a constant temperature for 8 hours, take out the sample and rinse it with ethanol for several times, and then wash it with deionized water for several times to obtain foamed iron with chain polythiolsuccinate propylene glycol loaded on the surface, which is recorded as intermediate A.
[0093] Step [2] The amino group of poly(propylene glycol mercapto succinate) is substituted and formed, which specifically comprises the following operations:
[0094] b1. The ammonium cerium nitrate, ammonium sulfamate, ferric nitrate and sec-butanol were added to deionized water to form a mixture of ammonium cerium nitrate concentration of 200 g / L, ammonium sulfamate concentration of 170 g / L, ferric nitrate concentration of 60 g / L, sec-butanol concentration of 90 mL / L of the replacement solution;
[0095] b2. Immerse intermediate A in the substitution liquid (the weight of intermediate A immersed in each liter of the substitution liquid is 90 g), heat to 50° C. in a water bath, and react for 2 hours to complete the amino substitution formation of the chain polythiolsuccinic acid propylene glycol on the surface of the foamed iron to obtain intermediate B.
[0096] Step [3] constructs cross-linked polyterephthalamide-thiosuccinate on the surface of the foamed iron matrix, specifically comprising the following operations:
[0097] c1. Add terephthalic acid and azobisisoheptanenitrile to dimethyl sulfoxide and mix to form a base solution (the amount of phthalic acid added per liter of the base solution is 210 g, and the amount of azobisisoheptanenitrile added is 90 g); add sulfamic acid to deionized water to form an additive solution having a sulfamic acid concentration of 120 g / L; add the additive solution to the base solution in a ratio of 3:4 by volume to form a construction solution;
[0098] c2. The intermediate B is immersed in the construction liquid (the weight of the intermediate B immersed in each liter of the construction liquid is 260 g), heated to 60° C. in a water bath, and reacted at a constant temperature for 6 hours to obtain a foamed iron with a surface loaded with cross-linked polyterephthalamide-mercaptosuccinate, and finally the adsorption material is obtained.
[0099] Example 4
[0100] Preferred embodiment 4 of the present invention provides a method for preparing an adsorbent material for treating cadmium ion wastewater, comprising the following steps performed in sequence:
[0101] Step [1] loading chain polythiosulfate propylene glycol succinate on the surface of the foamed iron matrix specifically comprises the following operations:
[0102] a1. Add mercaptosuccinic acid, 1,3-propylene glycol and ethane sulfonic acid to deionized water to form an inorganic base liquid having a mercaptosuccinic acid concentration of 135 g / L, a 1,3-propylene glycol concentration of 135 mL / L and an ethane sulfonic acid concentration of 60 mL / L; cumene hydroperoxide and propylbenzene are added to anhydrous ethanol to form an organic additive liquid having a cumene hydroperoxide concentration of 55 mL / L and a propylbenzene concentration of 15 mL / L; the organic additive liquid is added to the inorganic base liquid in a volume ratio of 1.5:8 to form a synthetic liquid;
[0103] a2. Immerse the foamed iron sample in the synthetic liquid (the weight of the foamed iron immersed in each liter of the synthetic liquid is 255 g), heat it to 60°C in a water bath, react for 10 hours at a constant temperature, take out the sample and rinse it with ethanol for several times, and then wash it with deionized water for several times to obtain foamed iron with chain polythiocaprolactone succinate loaded on the surface, which is recorded as intermediate A.
[0104] Step [2] The amino group of poly(propylene glycol mercapto succinate) is substituted and formed, which specifically comprises the following operations:
[0105] b1. The ammonium cerium nitrate, ammonium sulfamate, ferric nitrate and sec-butanol were added to deionized water and mixed to form a cerium ammonium nitrate concentration of 180 g / L, ammonium sulfamate concentration of 120 g / L, ferric nitrate concentration of 70 g / L, sec-butanol concentration of 70 mL / L of the replacement solution;
[0106] b2. Immerse intermediate A in the substitution liquid (the weight of intermediate A immersed in each liter of the substitution liquid is 70 g), heat to 45° C. in a water bath, and react for 3 hours to complete the amino substitution formation of the chain polythiolsuccinic acid propylene glycol on the surface of the foamed iron to obtain intermediate B.
[0107] Step [3] constructs cross-linked polyterephthalamide-thiosuccinate on the surface of the foamed iron matrix, specifically comprising the following operations:
[0108] c1. Add terephthalic acid and azobisisoheptanenitrile to dimethyl sulfoxide and mix to form a base solution (the amount of phthalic acid added per liter of the base solution is 175 g, and the amount of azobisisoheptanenitrile added is 60 g); add sulfamic acid to deionized water to form an additive solution having a sulfamic acid concentration of 130 g / L; add the additive solution to the base solution in a ratio of 2:3 by volume to form a construction solution;
[0109] c2. The intermediate B is immersed in the construction liquid (the weight of the intermediate B immersed in each liter of the construction liquid is 220 g), heated to 70° C. in a water bath, and reacted at a constant temperature for 5 hours to obtain a foamed iron with a surface loaded with cross-linked polyterephthalamide-mercaptosuccinate, and finally the adsorption material is obtained.
[0110] The above are only preferred embodiments of the present invention. It should be understood that the description of the above embodiments is only used to help understand the method and core ideas of the present invention, and is not used to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, etc. made within the ideas and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing an adsorbent material for treating cadmium ion wastewater, characterized in that: It contains the following steps in order: Step [1] Loading chain polythiocarboxylic acid propylene glycol on the surface of the foamed iron matrix; Step [2] Substitution of the amino group of poly(propylene glycol mercapto succinate); Step [3] constructs cross-linked poly(terephthalamide)-mercaptosuccinate on the surface of the foamed iron matrix to obtain the adsorption material.
2. A method for preparing an adsorbent material for treating cadmium ion wastewater according to claim 1, characterized in that: The step [1] specifically includes the following operations: a1. Add mercaptosuccinic acid, 1,3-propylene glycol and ethane sulfonic acid to deionized water and mix to form an inorganic base liquid; add cumene hydroperoxide and propylbenzene to anhydrous ethanol and mix to form an organic additive liquid; add a certain amount of organic additive liquid to the inorganic base liquid and mix to form a synthetic liquid; a2. Immerse the foamed iron sample in the synthetic solution, heat it in a water bath to 50-70°C, react at a constant temperature for 8-12 hours, remove the sample and rinse it with ethanol several times, and then wash it with deionized water several times to obtain a foamed iron with a surface loaded with chain polythiosulfate propylene glycol, recorded as intermediate A.
3. A method for preparing a cadmium ion wastewater adsorbent material according to claim 2, characterized in that: In step a1, the concentration of mercaptosuccinic acid in the inorganic base liquid is 120g / L-150g / L, the concentration of 1,3-propylene glycol is 100mL / L-170mL / L, and the concentration of ethanesulfonic acid is 40mL / L-80mL / L; the concentration of cumene hydroperoxide in the organic additive liquid is 40mL / L-70mL / L, and the concentration of propylbenzene is 10mL / L-20mL / L; the volume ratio between the organic additive liquid and the inorganic base liquid in the synthetic liquid is 1-2:7-9.
4. A method for preparing a cadmium ion wastewater adsorbent material according to claim 2, characterized in that: In step a2, the weight of the foamed iron immersed in each liter of the synthetic liquid is 230-270 g.
5. A method for preparing an adsorbent material for treating cadmium ion wastewater according to claim 1, characterized in that: The step [2] specifically includes the following operations: b1. Add cerium ammonium nitrate, ammonium sulfamate, ferric nitrate and sec-butyl alcohol to deionized water and mix to form a replacement solution; b2. Immerse the intermediate A in the substitution solution, heat in a water bath to 40-50°C, and react for 2-4 hours to complete the amino substitution formation of the chain polythiolsuccinic acid propylene glycol on the surface of the foamed iron to obtain the intermediate B.
6. A method for preparing an adsorbent material for treating cadmium ion wastewater according to claim 5, characterized in that: The concentration of ammonium cerium nitrate in the replacement solution is 160g / L-200g / L, the concentration of ammonium sulfamate is 80g / L-170g / L, the concentration of ferric nitrate is 60g / L-80g / L, and the concentration of sec-butyl alcohol is 50mL / L-90mL / L.
7. A method for preparing an adsorbent material for treating cadmium ion wastewater according to claim 5, characterized in that: In step b2, the weight of the intermediate A immersed in each liter of the replacement liquid is 50-90 g.
8. The method for preparing an adsorbent material for treating cadmium ion wastewater according to claim 1, characterized in that: The step [3] specifically includes the following operations: c1. Adding terephthalic acid and azobisisoheptanenitrile to dimethyl sulfoxide, mixing to form a base liquid; adding sulfamic acid to deionized water, mixing to form an additive liquid; adding a certain amount of the additive liquid to the base liquid, mixing to form a construction liquid; c2. Immerse the intermediate B in the construction solution, heat it to 60-80° C. in a water bath, and react at a constant temperature for 4-6 hours to obtain a foamed iron having a surface loaded with cross-linked polyterephthalamide-mercaptosuccinate, which is the adsorption material.
9. A method for preparing an adsorbent material for treating cadmium ion wastewater according to claim 8, characterized in that: In step c1, the amount of phthalic acid added to each liter of the base liquid is 140-210 g, and the amount of azobisisoheptanenitrile added is 30-90 g; the concentration of aminosulfonic acid in the additive liquid is 120 g / L-140 g / L; and the volume ratio between the additive liquid and the base liquid in the construction liquid is 1-3:3-4.
10. The method for preparing an adsorbent material for treating cadmium ion wastewater according to claim 8, characterized in that: In step c2, the weight of the intermediate B immersed in each liter of the construction solution is 180-260 g.
